PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA ARAB MELALUI PENDEKATAN KOMUNKATIF - Muspika Hendri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This article describes the Arabic learning in terms of speaking skills using communicative approach. In Arabic language learning is known four language skills that must be possessed by students that are listening skills (maharah al-istima '), speaking skill (maharah al-kalam), reading skill (maharah al-qira`ah), writing skill (maharah al-kitabah ). To obtain language skills in the learning process and become a daily habit in the environment would require the competence of Arabic teachers who have an innovative approach in teaching. One of the approaches of learning speaking skills is by using a communicative approach. The steps are (1) the learner hears, reads, then practices a two-line dialogue with his partner, (2) hears and repeats it, (3) listens to the dialogue model and then repeats it by observing the names in the dialog with their own name, (4) ) read the question hint and make a question, (5) read a two-line dialogue framework then practice with his partner, (6) hear reading the question model and ask.